Типові хиби ремаркування галузевої лексики в загальномовному тлумачному словнику - Балог, В.О. (Лексикографічний бюлетень, 2013)
This paper presents a scheme typical drawbacks of functional and stylistic characteristics of industry vocabulary in a general explanatory dictionary developed based on the analysis of the basic vocabulary of modern Ukrainian language. Keywords: industrial vocabulary, general language dictionary, note.